Respiration artifact correction in three‐dimensional proton resonance frequency MR thermometry using phase navigators. Issue 1 (13th August 2015) - Svedin, Bryant T.; Payne, Allison; Parker, Dennis L.
Abstract : Purpose: To develop reliable three‐dimensional (3D) segmented echo planar imaging (seg‐EPI) proton resonance frequency (PRF) temperature monitoring in the presence of respiration‐induced B0 variation. Methods: A free induction decay (FID) phase navigator was inserted into a 3D seg‐EPI sequence before and after EPI readout to monitor B0 field variations. Using the field change estimates, the phase of each k‐space line was adjusted to remove the additional phase from the respiratory induced off‐resonance. This correction technique was evaluated while heating with MR‐guided focused ultrasound (MRgFUS) in phantoms with simulated breathing and during nonheating conditions in healthy in vivo breasts. Results: With k‐space phase correction, the standard deviation of magnitude images and PRF temperature measurements in breast from five volunteers improved by an average factor of 1.5 and 2.1, respectively. Improved accuracy of temperature estimates was observed after correction while heating with MRgFUS in phantoms. Conclusion: Phase correction based on two FID navigators placed before and after the echo train provides promising results for implementing 3D monitoring of thermal therapy treatments in the presence of field variations due to respiration. Magn Reson Med 76:206–213, 2016. © 2015 Wiley Periodicals, Inc.